PENGARUH GINI RATIO, PDRB PERKAPITA DAN TINGKAT INFLASI TERHADAP TINGKAT KEMISKINAN DI PROVINSI SUMATERA UTARA - Hastina Febriaty (Quantitative Economics Journal, 2017)
Poverty is a living condition that is in shortage experienced by a person or household so as not being able to meet the minimal or decent needs for his life. And poverty is a social problem that is always present in the midst of society.In this research discusses the influence of Gini Ratio, Per Capita GDP and Inflation Rate to Poverty Level in North Sumatera Province. The purpose of this research is to know the influence of Gini Ratio, PDRB / Kapita and Inflation rate to poverty level in North Sumatera province, partially and simultaneously, and the dominant influence variable to poverty level in North Sumatera Province. Sources of data used are secondary data taken from the Central Bureau of Statistics and Bank of Indonesia from 2001 to 2016.Teknik analysis used in this research is multiple linear regression analysis using e-views program 8.1 and perform testing classical assumptions and using hypothesis testing simultaneously (F) and partial (t). The results showed that partially Gini Ratio and PDRB / Kapita have negative and significant effect to poverty level in North Sumatera Province while inflation rate have positive and insignificant effect to poverty level in North Sumatera Province simultaneously Gini Ratio, PDRB Perkapita and inflation rate have significant effect of poverty level in North Sumatera Province.